Autologous retinal pigment epithelium–choroid sheet transplantation in age related macular degeneration: morphological and functional results. Issue 3 (11th October 2006) - Treumer, Felix; Bunse, Arnd; Klatt, Carsten; Roider, Johann
Abstract : Objective: To evaluate the outcome of autologous retinal pigment epithelium (RPE)–choroid sheet transplantation after removal of a subfoveal choroidal neovascularisation (CNV) in patients with age related macular degeneration (AMD). Methods: RPE–choroid sheet transplantation was performed in 10 consecutive patients with exudative AMD (n = 9) or geographic atrophy (n = 1). After CNV extraction, an autologous RPE–choroid patch was translocated from the midperiphery under the macula. Follow-up was between 6 and 12 months. Visual acuity testing and microperimetry (Nidek-MP1) as well as autofluorescence, fluorescein and indocyanine green (ICG) angiography were performed and the data were analysed retrospectively. Results: Visual acuity (logarithm of minimum angel of resolution) before operation ranged from 0.7 to 1.8 (mean 1.37) and after operation from 0.4 to 1.6 (mean 1.24). Visual acuity after operation improved in seven patients (by a mean of 0.26), remained stable in one patient and decreased in two patients. Microperimetry showed light sensitivity and fixation on the sheet in five cases. ICG angiography demonstrated perfusion through the RPE–choroid graft in nine patients. Postoperative complications included retinal detachment (n = 1) and epiretinal membrane formation (n = 2). The patient with geographic atrophy developed a CNV after surgery. Conclusions: Autologous RPE–choroid sheet transplantation is feasible and a comparatively safe procedure. Microperimetry showed fixation and light perception over the graft with a moderate increase in mean visual acuity.